2016
DOI: 10.1016/j.anifeedsci.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rumen contents’ processing method on microbial populations in the fluid and subsequent in vitro fermentation of substrates of variable composition

Abstract: a b s t r a c tThe in vitro batch culture technique is being increasingly used to study rumen fermentation, but the results are affected by several factors, being the source of the inoculum one of the most relevant. This work was conducted to assess the effects of different processing methods of ruminal contents on microbial populations in the obtained fluid, and its influence on fermentation parameters when the fluid was used as inoculum for in vitro incubations. Rumen contents were obtained from four rumen-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Gas production was measured at 9 and 24 h, and a 15 mL sample of the gas was collected in vacuum tubes and stored at room temperature until CH 4 analysis. Sampling at 9 h of incubation was chosen because previous studies from our group [ 13 , 14 ] showed that in vitro CH 4 production is very low at shorter incubation times. Samples of all experimental diets were incubated in one run using one vial per sample.…”
Section: Methodsmentioning
confidence: 99%
“…Gas production was measured at 9 and 24 h, and a 15 mL sample of the gas was collected in vacuum tubes and stored at room temperature until CH 4 analysis. Sampling at 9 h of incubation was chosen because previous studies from our group [ 13 , 14 ] showed that in vitro CH 4 production is very low at shorter incubation times. Samples of all experimental diets were incubated in one run using one vial per sample.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, study on rumen fermentation by in vitro batch culture has been increased, yet the diet, rumen processing method and the sampling time of donor rumen contents remains as a foremost regulating factor. Subsequently, Mateos et al [ 154 ] studied the outcome of three diverse rumen fluid processing technique based on rumen microbiota population and its effect on in vitro anaerobic fermentation parameters. In this study, four sheep with fistulae rumen was fed with alfalfa hay and concentrate diet (2:1), later the rumen content were subjected to the processing methods like SQ (Squeezed by four layer of cheese cloth); FL (SQ + nylon cloth (100 µm) filtration) and STO (Stomacher® blending + SQ).…”
Section: Role Of Microbes and Different Process Strategies Adopted For Biofuel Productionmentioning
confidence: 99%